2010
DOI: 10.1111/j.1365-2621.2010.02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐induced gels of soy protein and κ‐carrageenan at different pH values

Abstract: Heat-induced (90°C ⁄ 30 min) gelling of soy protein isolate (SPI) and j-carrageenan (j-CR) systems at pH values of 6.7 and 5.7 was evaluated. j-CR addition, increase in protein concentration and reduction in pH led to decreases in the initial gel structure forming temperature. Self-supporting gels were not formed at concentrations of 8% (w ⁄ w) SPI or at concentrations below 0.3% (w ⁄ w) j-CR, but an increase in the concentration of SPI and j-CR led to an increase in the stress at rupture without influencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…Among them, nonmeat ingredients and additives have become more and more popular because of their better functional properties and relatively reasonable cost compared to lean meat (Şükrü and Osman 2012;Youssef and Barbut 2011). Meanwhile, these ingredients and additives could improve yield, gelling properties, textural quality, flavor, and overall acceptability (Cavallieri et al 2010;Chin et al 1999;Sheridan and Shilton 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Among them, nonmeat ingredients and additives have become more and more popular because of their better functional properties and relatively reasonable cost compared to lean meat (Şükrü and Osman 2012;Youssef and Barbut 2011). Meanwhile, these ingredients and additives could improve yield, gelling properties, textural quality, flavor, and overall acceptability (Cavallieri et al 2010;Chin et al 1999;Sheridan and Shilton 2002).…”
Section: Introductionmentioning
confidence: 98%
“…However, the 11S soy protein fraction spray dried at 150 • C or 180 • C did not form self-supporting gels at pH 7, and hence these gels were not analysed. Cavallieri et al (2010) identified that systems containing 8% soy protein isolate (SPI) did not form self-supporting gels at pH 6.7, but formed at pH 5.7 (pH value closer to the isoelectric point). Thus, in addition to the interactions due to heat denaturation, greater proximity to the isoelectric point favour protein-protein interactions due to reduction in electrostatic repulsion.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…These properties vary with protein component, protein concentration, ionic strength, dielectric constant of the medium, interactions with other macromolecules, as well as processing conditions such as pH, temperature, pressure, enzymatic treatment, etc. (Cavallieri, Garcez, Takeuchi, & da Cunha, 2010;Howard & Udenigwe, 2013;Kim, Weller, Hanna, & Gennadios, 2002). In recent years, research efforts in broadening functionalities of SPI (Chen, Zhao, Sun, Ren, & Cui, 2013;Fernandez-Avila, Escriu, & Trujillo, 2015;Gan, Cheng, & Easa, 2008;Shen & Tang, 2012) have increased the need of clarifying its multi-level structural responses under various processing conditions.…”
Section: Introductionmentioning
confidence: 99%